Corrections to “Water-Resistant Smartphone Technologies” - Quanqing Yu; Rui Xiong; Chuan Li; Michael G. Pecht (IEEE Access, 2024)
In the above article [1], the authors want to update the definition of fresh water provided in Sections II and VI based on discussions with the IEC.